As representações dos professores de Língua Portuguesa acerca do Regime de Progressão Continuada (RPC) e suas implicações para construção do letramento literário - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The objective of this work is to understand the social representations of Portuguese language teachers about the PRC and its implications for the construction of literary literacy of students of elementary school II in a state school in the municipality of Humaitá/AM. This research is linked to the line of research Theoretical-Methodological Perspectives for Science Teaching of the Graduate Program in Science and Humanities Teaching at the Vale do Rio Madeira Campus at the Federal University of Amazonas. We adopted the social representations in this research because we understand that through the teachers' speech it is possible to understand the development of the RPC in everyday pedagogical practice. For its realization, we used a qualitative and exploratory approach, which allowed interaction with the subjects, providing spontaneous and realistic speeches. As a methodological resource for data collection, the Case Study (YIN, 2001) was used and for the analysis the Theory of Social Representations of Moscovici (2015), which allowed the interpretation and understanding of the speeches, their meanings and conventionalizations, concretized from interview and observation. To understand the study theme, preference was given to the theoretical framework on the RPC: educational legislation (laws, guidelines, ordinances), Bezerra (2015), Ferreira (2006), Jeffrey (2011), Souza e Silva (2001), Guilherme (2006), Catani (2000), among others; Portuguese language and literary literacy: Sena (2001), Basso and Gonçalves (2014), Fiorin (2019), Paulino and Cosson (2009), Soares (2004); assessment and learning assessment: Luckesi (2011), Hoffmann (2001), Silva and Hoffman (2003), Depresbiteris (2004). The subjects who participated in the research are five Portuguese language teachers who work in the state school system in Humaitá-Amazonas. After data collection, it was possible to categorize the results, which showed that: in the context in which the RPC is developed, evaluation has become the primary responsibility of teachers, demonstrating a strong presence of traditionalism, since they are aware of how a practice should be evaluative with a focus on learning, but continue to measure students' knowledge through grades; teachers have a reduced concept of evaluation, therefore of the RPC; there are impacts on the development of RPC in schools, where public authorities and school management require approvals, placing more emphasis on results than on the diagnosis of learning, leading teachers to use their own initiatives to improve the quality of teaching; there is an absence of support from school management and a lack of financial resources that are not available, there is no way to offer education that fully promotes reading and writing practices at school. The inadequate development of the RPC at school can produce serious consequences, such as the presence of illiterate students in elementary school II, which violates the rights of training for the critical exercise of citizenship.
Keywords: Professores - Formação; Prática pedagógica; Aprendizagem centrada no aluno; Letramento; Língua portuguesa - Aprendizagem; CIÊNCIAS HUMANAS; Progressão Continuada; Professores; Língua Portuguesa; Avaliação; Letramento literário